Agents in Child Marriage Practice in Rural West Java - Novitha Syari Dhevi Pradipta; Ekawati Sri Wahyuni; Titik Sumarti (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2019)
The prevalence of child marriage in Indonesia, although it has declined over the last three decades, remains in a high rate. Child marriage is indirectly legitimated by the Indonesian Marriage Law of 1974 which states that the minimum age limit of the bride shall be 16 years old. This is contrary to the Constitution of the Republic of Indonesia and the Child Protection Law. Child marriages in rural areas are not only driven by structures like family and society but are also initiated by individual actions driven by the agency. Therefore, this study examined child marriage practice comprehensively through the perspective of Giddens's structuration. This study aimed to identify the agents in child marriage practice. The results of the study found that there are two types of child marriages in rural areas. The first one is registered and the other is unregistered marriage. The identified agents in child marriage practice are girls, amil (assistant of marriage recording officer), Religious Affairs (KUA) officers, peer groups, teachers, mothers, and spouses. Each agent's action is affected by both structure and agency. Girl's actions are influenced by the agency. The girls are able to do agency in and through social practice. Girls’ agency produces meaningful action understood as a process and inherent to the agent through reflexive monitoring. Meanwhile, the actions of other identified agents are influenced by the existing structures in the society. Agent’s actions perpetuate child marriage practice. Child marriage practice occurs because there is no family strength. Therefore, the improvement of the family strength is needed as a constraining structure.